The practice of strategic journal self-citation: It exists, and should stop (A note from the editor-in-chief) - Chorus, Caspar G. (European Journal of Transport and Infrastructure Research, 2015)
This note highlights how journal self-citation practices substantially influence impact factorbased journal rankings in the field of Transportation. Furthermore, by means of analyzing Thomson Reuters’ most recent Journal Citation Report (JCR), I show that a substantial share of these self-citations is likely to be the result of strategic behavior by editors of journals. I conclude with a call to editors to stop requesting or nudging authors to add journal self-citations to their papers; and a call to authors to stop giving in to editors when being asked to provide such citations.